Systemic therapy with pemigatinib and sintilimab followed by resection for recurrent FGFR-2-positive intrahepatic cholangiocarcinoma: a case report - Yuchen Yang; Jingfeng Li; Di Ma; Fengjie Hao; Weixia Li; Jing Xie; Lihan Qian; Junqing Wang; Yongjun Chen (Frontiers in Oncology)
BackgroundFibroblast growth factor receptor-2 (FGFR-2) mutations are frequently observed in intrahepatic cholangiocarcinoma (ICC). While FGFR2-targeted therapies are primarily studied in advanced ICC, this report presents a rare case of locally recurrent ICC treated with systemic therapy, leading to significant tumor regression and successful R0 resection.Case presentationA 51-year-old female underwent right posterior hepatectomy and cholecystectomy in 2018 for ICC. In August 2022, postoperative MRI revealed tumor recurrence near the hepatic vein, accompanied by intrahepatic bile duct dilation and a tumor thrombus. Given the tumor’s proximity to critical structures and confirmed FGFR-2 fusion, systemic therapy with pemigatinib and sintilimab was initiated. After four cycles, the tumor showed partial remission, with a reduction in the bile duct tumor thrombus. In May 2023, the patient underwent successful right hemi-hepatectomy. Postoperatively, she continued combination therapy without recurrence or metastasis for 19 months.ConclusionThis case highlights the efficacy of pemigatinib-based systemic therapy in achieving tumor regression and enabling curative resection in locally recurrent FGFR-2-positive ICC. The successful outcome underscores the potential of targeted therapies in managing recurrent ICC, warranting further investigation.